Immune-related adverse events and their effects on survival outcomes in patients with non-small cell lung cancer treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Liang, Yuxiang; Xu, Haidi; Liu, Futao; Li, Lei; Lin, ChenXi; Zhang, Yaozhong; Wang, Na; Wang, Lei (Frontiers in Oncology, 2024)
BACKGROUND: The use of immune checkpoint inhibitors (ICIs) has become the standard of care for non-small cell lung cancer. The purpose of this study was to systematically review the literature to determine whether the occurrence of immune-related adverse events (irAEs) following the use of ICIs predicts different clinical outcomes in non-small cell lung cancer (NSCLC). METHODS: Relevant studies from the time of database creation to July 20, 2023, were systematically searched to explore the differences in clinical outcomes in patients with advanced NSCLC with or without irAEs. The outcome indicators included the occurrence of irAEs, progression-free survival (PFS), and overall survival (OS).RESULTS: 25 studies met the inclusion criteria. Of these studies, 22 reported the effect on OS, and 19 reported the effect on PFS. The results showed that for patients with NSCLC, the occurrence of irAEs after receiving immunotherapy showed a statistically significant benefit over the absence of irAEs for OS (HR=0.55,95% CI=0.46-0.65) and PFS (HR=0.55 95% CI=0.48-0.64), but severe irAEs (grades 3-5) were associated with worse OS (HR=1.05, 95% CI=0.87-1.27). Compared with gastrointestinal, lung, and hepatitis, irAEs of the skin and endocrine system tend to predict better OS and PFS.CONCLUSION: The occurrence of irAEs,especially mild and early irAEs,indicates better OS and PFS in patients with NSCLC treated with ICIs, irrespective of patient characteristics, type of ICIs, and irAEs. However, Grade 3 or higher toxicities resulted in worse OS.